All Days 1993
DOI: 10.2118/25466-ms
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hydraulic Fracture Direction, San Juan Basin, New Mexico

Abstract: Reservoir management of hydraulically fractured reservoirs can be improved with knowledge of the orientation of hydraulic fractures. Fracture direction can affect where wells are placed, the design of well patterns for EOR floods, the design of fracture treatments, and the stability and fracturing of horizontal wells. This paper presents a field study of the determination of hydraulic fracture direction in the San Juan basin in northwest New Mexico. Data from six different fracture direction techniques were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There is strong local evidence for NE-SW trending stresses at the southeastern corner of the basin (Yale et al, 1993; conjugate deformation bands in the San Ysidro area as described below) and in the Dakota outcrops at the northern edge of the basin (also described below). These may be related to late-Laramide, southwestward-directed overthrusting of the Nacimiento uplift and San Juan uplift respectively, due ultimately to the late-Laramide re-orientation of plate motions reconstructed by Bird (1998).…”
Section: Kinematic Model Of Stresses and Structural Elementsmentioning
confidence: 88%
See 1 more Smart Citation
“…There is strong local evidence for NE-SW trending stresses at the southeastern corner of the basin (Yale et al, 1993; conjugate deformation bands in the San Ysidro area as described below) and in the Dakota outcrops at the northern edge of the basin (also described below). These may be related to late-Laramide, southwestward-directed overthrusting of the Nacimiento uplift and San Juan uplift respectively, due ultimately to the late-Laramide re-orientation of plate motions reconstructed by Bird (1998).…”
Section: Kinematic Model Of Stresses and Structural Elementsmentioning
confidence: 88%
“…The only published results of a study designed specifically to determine the present-day stress orientations (Yale et al, 1993) found a consistently NE-SW trend for the maximum horizontal compressive stress in four wells in one field. This field is located near Cuba, in the southeastern corner of the basin (Yale, personal communication, 1998).…”
Section: Subsurface Stressesmentioning
confidence: 99%